Analisis Pengendalian Kualitas Produk Plastik Injeksi dengan Menggunakan Metode Statistical Process Control (SPC) dan Kaizen di CV. Gradient Kota Bandung - Mahaputra, M. Syafaruddin (Media Nusantara, 2021)
Product quality is an absolute requirement to compete in the global era. Quality control is done to maintain and improve product quality in accordance with company standards and consumer desires. CV Gradient Bandung is a company engaged in the field of plastic especially plastic injection. The production system used by this company is make to order so that the number and specifications of the products vary according to the customer’s wishes. This study aims to determine how the analysis of quality control using Statistical Process Control (SPC) and kaizen. The analysis shows that quality control is in a state of uncontrolled or still experiencing irregularities. The most type of disability is 7715 pcs short mold. From the cause and effect diagram it can be seen that the factors causing product defects are human, machine, mold, raw material, and environmental factors. Based on the tools of kaizen implementation in the form of 5S (seiri, seiton, seiso, seiketsu, shitsuke) and 5W + 1H (what, why, where, when, who, how), the recommended improvement obtained is the holding of more stringent supervision and control in machine and mold maintenance, more careful in the selection of raw materials, cleanliness and comfort of the production site, and provide training for employees to have sufficient skills.